Identification of Thiols in Yellow Onion (Allium cepa L.) Using Solvent Vented Large Volume Injection GC‐MS. Issue 11 (20th October 2017) - Wermes, Clint; Cannon, Robert; Haasnoot, Sytze; Colstee, Hans; Niedeveld, Cor; Koopmanschap, Gijs; Da Costa, Neil C.
Abstract: Thiols are often highly odor active molecules and as such can significantly contribute to aroma while being present at extremely low concentrations. This paper details the identification of thiols in yellow onion juice by solvent extraction followed by thiol enrichment using a mercuric agarose gel column. Due to the inherent thermal instability and low concentrations of thiols in onion, chromatographic analysis utilized larger volume solvent elimination injections. New sulfur compounds in onion included 1, 1‐propanedithiol, bis‐(1‐sulfanylpropyl)‐sulfide, 1‐methylsulfanyl‐1‐propanethiol, 1‐propylsulfanyl‐1‐propanethiol, and 1‐allylsulfanyl‐1‐propanethiol. A discussion on the potential route of formation for each compound is included along with the orthonasal and retronasal evaluations of the synthesized molecules. This work investigated and identified 5 newly identified compounds present in onions that can impart onion character at low concentrations levels.